Can plant-derived anti-HIV compounds be used in COVID-19 cases?. (September 2022) - Das, Diptimayee; Bihari Jena, Atala; Banerjee, Antara; Kumar Radhakrishnan, Arun; Duttaroy, Asim K.; Pathak, Surajit
Abstract: People living with HIV are more exposed to the adverse health effects of the worldwide COVID-19 pandemic. The pandemic's health and social repercussions may promote drug abuse and inadequate HIV management among this demographic. The coronavirus pandemic of 2019 (COVID-19) has caused unprecedented disruption worldwide in people's lives and health care. When the COVID-19 epidemic was identified, people with HIV faced significant obstacles and hurdles to achieving optimal care results. The viral spike protein (S-Protein) and the cognate host cell receptor angiotensin-converting enzyme 2 (ACE2) are both realistic and appropriate intervention targets. Calanolides A, Holy Basil, Kuwanon-L, and Patentiflorin have anti-HIV effects. Our computational biology study investigated that these compounds all had interaction binding scores related to S protein of coronavirus of −9.0 kcal /mol, −7.1 kcal /mol, −9.1 kcal /mol, and −10.3 kcal/mol/mol, respectively. A combination of plant-derived anti-HIV compounds like protease inhibitors and nucleoside analogs, which are commonly used to treat HIV infection, might be explored in clinical trials for the treatment of COVID-19.